Takaful Rules and Regulations for ASEAN Countries: Takaful Player Perspective - Wan Norhayate, Wan Daud; Fakhrul Anwar, Zainol; Fauzilah, Salleh; Ahmad Shukri, Yazid; Suraya, Ismail; Ruzian, Markom; Nur Dalila, Mukhtar (2017)
Each country applies their own rules and regulation and it is usually different when researcher compares one country to another. This paper intends to identify the takaful rules and regulations for Malaysia and Indonesia and to analyse the similarities and differences of takaful rules and regulations for both countries. In order to achieve these research objective, a case study on a leading takaful operator was undertaken. This study begins with the introduction of brief background of an ABC leading takaful operator. The main findings of this research include: Takaful rules and regulations of Malaysia and Indonesia are governed by Islamic Financial Services Act 2013 (IFSA 2013) and Undang-Undang No 40 (UU40) respectively; IFSA (2013) is a special Shariah compliance guidelines for financial services including takaful whereas UU40 focus on takaful and insurance service. The results of this research could provide a significant contribution to takaful operators in ASEAN countries especially Malaysia and Indonesia.